2009
DOI: 10.1186/1745-0179-5-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the evidence of the burden of bipolar disorder in Europe

Abstract: BackgroundBipolar disorder is recognized as a major mental health issue, and its economic impact has been examined in the United States. However, there exists a general scarcity of published studies and lack of standardized data on the burden of the illness across European countries. In this systematic literature review, we highlight the epidemiological, clinical, and economic outcomes of bipolar disorder in Europe.MethodsA systematic review of publications from the last 10 years relating to the burden of bipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 52 publications
5
92
2
4
Order By: Relevance
“…studies 11 Meta‐analysis: yes Adults Range: 2417–43,093 General population samples/surveys Community settings Mostly US studies Validated screening tool/standardized measurement toolsPrev: 37.4% Ho 2014 Search: 2012 # incl. studies 8 Meta‐analysis: yes Age 10+ 1641 patients with internet addition (IA) and 11,210 controls without IA Postal survey, students, respondents to ads Community settings Mostly Asian samples Standard questionnaires, symptom checklists, interviews Prev of anxiety in IA patients vs normal controls: 23.3% (95% CI: 14.8–34.8) vs 10.3% (5.0–19.9) Anxiety most prev in young age groups with IA (19–39 years highest burden) Other mental and neurological disorders Fajutrao 2009 Search: past 10 years # incl. studies 26 Meta‐analysis: no Patients with bipolar disorder Range: 72–1,631,462 Surveys; general population, inpatients Clinical and community settings European studies DSM diagnoses 13–28% of bipolar patients with anxiety GAD and PD common 70%, 24%, 16% for Italy, France, Germany Amerio 2014 Search: Mar 2013 # incl.…”
Section: Embasementioning
confidence: 99%
See 1 more Smart Citation
“…studies 11 Meta‐analysis: yes Adults Range: 2417–43,093 General population samples/surveys Community settings Mostly US studies Validated screening tool/standardized measurement toolsPrev: 37.4% Ho 2014 Search: 2012 # incl. studies 8 Meta‐analysis: yes Age 10+ 1641 patients with internet addition (IA) and 11,210 controls without IA Postal survey, students, respondents to ads Community settings Mostly Asian samples Standard questionnaires, symptom checklists, interviews Prev of anxiety in IA patients vs normal controls: 23.3% (95% CI: 14.8–34.8) vs 10.3% (5.0–19.9) Anxiety most prev in young age groups with IA (19–39 years highest burden) Other mental and neurological disorders Fajutrao 2009 Search: past 10 years # incl. studies 26 Meta‐analysis: no Patients with bipolar disorder Range: 72–1,631,462 Surveys; general population, inpatients Clinical and community settings European studies DSM diagnoses 13–28% of bipolar patients with anxiety GAD and PD common 70%, 24%, 16% for Italy, France, Germany Amerio 2014 Search: Mar 2013 # incl.…”
Section: Embasementioning
confidence: 99%
“…use of social media) Original Heterogeneity: age of sample, different psychiatric questionnaires, mostly cross‐sectional studies, uncontrolled confounding (ex. environmental stress, parenting) Young patients mainly from Asian countries Review Small number of studies Unable to assess how estimates differ with use of self‐reported questionnaires vs. structured interviews 8 Other mental and neurological disorders Fajutrao 2009 Search: past 10 years # incl. studies 26 Meta‐analysis: no Bipolar disorder in Europe Original studies Anxiety assessment and reporting methods diff Retrospective and nonrepresentative samples Review Focus on electronic databases; language selection criteria 5 Amerio 2014 Search: Mar 2013 # incl.…”
Section: Embasementioning
confidence: 99%
“…In the United Kingdom, lifetime prevalence per 100 000 population is estimated at up to 10 000 for major depression 17 and approximately 1 000 for BD 18, compared with 400–1 000 for schizophrenia 19 and 200 for both MS and PD 20. Despite the greater research focus on cognitive function in schizophrenia and neurological disorders, it is clear that the higher prevalence of mood disorders in the population means that the absolute number with associated cognitive impairment is likely to be substantial and of significant public health importance.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the prevalence of bipolar disorder has been estimated at ~1% of the population [3], with a total cost of £342 million to the NHS at 2009/2010 prices, and hospitalization accounting for £207 million of that figure [1]. Various drugs are available as part of long-term treatment of bipolar disorder, designed to prevent relapse or recurrence [4].…”
Section: Introductionmentioning
confidence: 99%